2016
DOI: 10.1177/1073191115602554
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Math Anxiety, Math Performance, Worry, and Test Anxiety on the Iowa Gambling Task and Balloon Analogue Risk Task

Abstract: Multiple studies have shown that performance on behavioral decision-making tasks, such as the Iowa Gambling Task (IGT) and Balloon Analogue Risk Task (BART), is influenced by external factors, such as mood. However, the research regarding the influence of worry is mixed, and no research has examined the effect of math or test anxiety on these tasks. The present study investigated the effects of anxiety (including math anxiety) and math performance on the IGT and BART in a sample of 137 undergraduate students. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Comprehensive studies tend to indicate discrepancies across patterns of results involving the BART (Bishara et al, 2009;Purcell et al, 2017;De Groot and Thurik, 2018;Canning et al, 2022). For example, Maner and colleagues (2007) reported effects of anxiety on risk-taking, while a later study did not find such association (Buelow and Barnhart, 2017). King and colleagues (2014) reviewed the associations between impulsivity and alcohol consumption and observed discrepancies among studies that involved the BART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comprehensive studies tend to indicate discrepancies across patterns of results involving the BART (Bishara et al, 2009;Purcell et al, 2017;De Groot and Thurik, 2018;Canning et al, 2022). For example, Maner and colleagues (2007) reported effects of anxiety on risk-taking, while a later study did not find such association (Buelow and Barnhart, 2017). King and colleagues (2014) reviewed the associations between impulsivity and alcohol consumption and observed discrepancies among studies that involved the BART.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of risk-taking behavior are interesting for both general and clinical research. In fact, such trait as indexed by BART scores has been associated with dysfunctional psychophysiological phenotypes, including anxiety (Maner et al, 2007;Buelow and Barnhart, 2017), clinical disorders (Hunt et al, 2005;Swogger et al, 2010;Dominguez et al, 2011;Cheng et al, 2012;Robbins et al, 2012;Reddy et al, 2014;Fischer et al, 2015;Brown et al, 2015;Luk et al, 2019;Tikasz et al, 2019;Boka et al, 2020), abuse of heavy drugs (Hopko et al, 2006;Vassileva and Conrod, 2019), smoking attitudes (Lejuez et al, 2003;Lejuez et al, 2005;Dean et al, 2011;Hanson et al, 2014), alcohol consumption and related symptoms (Skeel et al, 2008;Fernie et al, 2010;Ashenhurst et al 2011;Weafer et al, 2011;DeMartini et al 2014;King et al, 2014), gambling (Holt et al, 2003;Mishra et al, 2017), risky sexual behavior (Lejuez et al, 2004;Bornovalova et al, 2008;Lawyer, 2013), and even with pandemic-related behavior (Guenther et al, 2021; for reviews on risk-taking and related dysfunctions see: Leigh, 1999;Turner et al, 2004;Isles et al, 2019). Moreover, BART use has been suggested as a potential marker for dissecting disease-related endophenotypes (Long et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the other measures, we did not find any effects of caffeine on performance in this task. Null effects are common with the IGT (Aklin et al, 2005;Lejuez et al, 2003aLejuez et al, , 2003bOverman et al, 2004) and many studies have shown that performance on the task can be influenced by contextual factors such as stress or mood (Buelow and Barnhart, 2015;Preston et al, 2007). Therefore, participants may have become more comfortable with the laboratory setting over time and this may have altered performance in the task.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread utilization of the BART is motivated by its capability in recreating an ecological experience to uncover (neuro)cognitive underpinnings of risk-taking in healthy subjects ( Lejuez et al, 2002 , 2003 , 2005 ; Weafer et al, 2011 ; De Groot, 2020 ; Guenther et al, 2021 ). However, measurements of risk-taking behavior are also interesting for clinical research since risk-taking indexed by BART scores has been associated with dysfunctional psychophysiological phenotypes, including anxiety ( Maner et al, 2007 ; Buelow and Barnhart, 2017 ), clinical disorders ( Hunt et al, 2005 ; Swogger et al, 2010 ; Dominguez, 2011 ; Cheng et al, 2012 ; Robbins et al, 2012 ; Reddy et al, 2014 ; Brown et al, 2015 ; Fischer et al, 2015 ; Tikàsz et al, 2019 ; Boka et al, 2020 ; Luk et al, 2021 ), abuse of heavy drugs ( Hopko et al, 2006 ; Vassilva and Conrod, 2019 ), smoking attitudes ( Lejuez et al, 2003 , 2005 ; Dean et al, 2011 ; Hanson et al, 2014 ), alcohol consumption and related symptoms ( Skeel et al, 2008 ; Fernie et al, 2010 ; Ashenhurst et al, 2011 ; Weafer et al, 2011 ; DeMartini et al, 2014 ; King et al, 2014 ), gambling ( Holt et al, 2003 ; Mishra et al, 2017 ), risky sexual behavior ( Lejuez et al, 2004 ; Bornovalova et al, 2008 ; Lawyer, 2013 ; for reviews on risk-taking and related dysfunctions see: Leigh, 1999 ; Turner et al, 2004 ; Isles et al, 2019 ). Moreover, BART use has been suggested as a potential marker for dissecting disease-related endophenotypes ( Long et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%